X-ray absorption of molecular cations—a new challenge for electronic structure theory. (7th September 2022) - Carravetta, V; Couto, R C; Ågren, H
Abstract: In this paper we put forward some historical notes on the development of computational chemistry toward applications of x-ray spectroscopies. We highlight some of the important contributions by Enrico Clementi as method and program developer and as a supporter of this branch of computational research. We bring up a modern example based on the very recent experimental development of x-ray absorption of cationic molecules. As we show this spectroscopy poses new challenges for electronic structure theory and the electron correlation problem.